Entrepreneurship Knowledge and Vocational Policy’s Effect on MSMEs Business Strategy: Artificial Intelligence Moderation Analysis - Idris, Muh. Ma’ruf; Mustafa, Muh. Yushar; Putra, Muh. Al Fatah Arief (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study investigates 122 culinary MSME owners in Makassar, Indonesia, to examine how entrepreneurship knowledge and vocational policy influence business strategy and analyze the moderating role of Artificial Intelligence (AI) in strengthening these relationships. Despite the growing interest in MSME development, limited research integrates human capital, institutional policy, and technological capability within a single strategic framework. Research Methodology: A quantitative approach was employed using a structured survey questionnaire distributed to MSME owners in the region. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS software. To enrich the interpretation, qualitative insights were obtained through in-depth interviews with selected stakeholders. The research framework was grounded in a comprehensive review of the entrepreneurship, institutional, and digital transformation literature. Results: The findings reveal that entrepreneurial knowledge positively and significantly influences business strategy development. Vocational policy does not have a significant direct effect on business strategy. Artificial intelligence demonstrates a significant direct effect and moderates the relationship between entrepreneurship knowledge and business strategy by strengthening innovation practices and strategic decision-making. Conclusions: Entrepreneurial knowledge is a critical strategic resource for MSMEs. However, institutional policy support alone is insufficient without technological capabilities. AI functions as a strategic enabler that amplifies the effective utilization of entrepreneurial expertise. Limitations: This study focuses on culinary MSMEs in Makassar, limiting the generalizability of the findings across sectors and regions. Contributions: This study advances the MSMEs and digital transformation literature by positioning AI as a strategic moderator linking knowledge and policy to competitive strategy.